Studi Gasifikasi Pengembangan Tongkol Jagung dengan Jerami Padi Menggunakan Reaktor Downdraft Dengan Dua Masukan Udara Tekan - Irawan, Ibnu; Samlawi, Achmad Kusairi; Budiarto, Hairil (Universitas Trunojoyo Madura, 2022)
The production of corn and rice produced by farmers in East Java has the potential to cause agricultural waste, therefore corn cobs are waste that requires special processing in order to be used optimally. Agricultural waste corn cobs and rice straw can be converted into gas fuel (Syngas). The purpose of this study was to determine the performance of gasification seen from the temperature distribution and composition of combustible gases such as CO, H2 and CH4. The downdraft gasifier type is used and applies the AR and E.R ratio to the temperature. For the pyrolysis and oxidation regions, the intake air varies (ARpir-oxi) 80%; 70%; and 0% at 14.5 air intake; 19.3; and 24.1 Nm3/hour from E.R 0.3, 0.4, and 0.5. Air intake in the adjust area using a valve. Temperature measurement using the type K thermocouple. The results show that the maximum temperature using ARpir-oks = 80%, the drying zone temperature is 187°C, the pyrolysis zone is 488°C, the oxidation zone is 895°C and the reduction zone is 585°C. Meanwhile, the highest production of CO gas is 20.50% and H2 gas is 14.55% using an ER of 0.4. Meanwhile, CH4 decreased for all ER values using ARpir-oks = 80%.